Investigasi City Branding Kota Padang Melalui Brand Attitude (Studi Kasus: Stakeholder) - Astri Yuza Sari; Sari Lenggogeni (Economac: Jurnal Ilmiah Ilmu Ekonomi, 2018)
Abstract This study aims to determine the effectiveness of Padang’s city brand "Padang Your Motherland" and find a city brand that is suitable for the Padang in the future by brand attitude. This research is a qualitative, which uses the city brand index by Anholt (Presence, Potential, Place, People, Pulse, Prerequisite) by interviewing 54 informants consisting of visitors (domestic and foreign) and non visitors (residents, entrepreneur). From the information obtained, they are analyzed thematically and validated by triangulation method. The result is less the effectiveness of Padang’s City brand "Padang Your Motherland" in the community, and found the factors that make city branding of Padang. However, the difference between visitors and non visitors, for domestic visitors, presence, place, pulse, and prerequisite variables are very influential in building city branding of Padang, whereas foreign visitors assume that the presence, place, people and pulse variables are influential in city branding of Padang. Resident assumed that only the pulse of building city branding of Padang, in line with that students assume that the pulse and place influential in forming city branding of Padang, but entrepreneurs have another view that not only the pulse and place that form city branding of Padang but also variable potential and people.